2005
DOI: 10.1007/s11663-005-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and seeding effects on the precipitation of scorodite from sulfate solutions under atmospheric-pressure conditions

Abstract: Arsenic is a major contaminant in the nonferrous extractive metallurgy. In the past 20 years, many studies have shown that it can be precipitated as relatively stable crystalline scorodite (FeAsO 4 • 2H 2 O) by precipitation under ambient or elevated pressures. In the present study, an extensive program of scorodite precipitation tests under ambient pressure has shown that the rate of scorodite formation increases dramatically by a small increase in temperature from 85 °C to 100 °C. The beneficial effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 8 publications
2
58
0
Order By: Relevance
“…Hollow bioscorodite seed particles were found increasingly filled with newly formed scorodite (Figure 4(a1-a6)), whilst solid chemical seeds induced their surface to be thoroughly coated with new scorodite precipitates (Figure 4(b1-b6)). Other abiotic studies under atmospheric pressure condition using As(V) and Fe(III) as starting species also have reported a positive effect of seeds with high specific surface area, e.g., the better scorodite precipitation kinetics were observed by using finer seeds such as hematite and hydrothermal scorodite [6]. Caetano et al (2009) reported that a specific surface area higher than 270 m 2 /g was required to achieve 85% As removal [16].…”
Section: Effect Of Seedmentioning
confidence: 94%
See 3 more Smart Citations
“…Hollow bioscorodite seed particles were found increasingly filled with newly formed scorodite (Figure 4(a1-a6)), whilst solid chemical seeds induced their surface to be thoroughly coated with new scorodite precipitates (Figure 4(b1-b6)). Other abiotic studies under atmospheric pressure condition using As(V) and Fe(III) as starting species also have reported a positive effect of seeds with high specific surface area, e.g., the better scorodite precipitation kinetics were observed by using finer seeds such as hematite and hydrothermal scorodite [6]. Caetano et al (2009) reported that a specific surface area higher than 270 m 2 /g was required to achieve 85% As removal [16].…”
Section: Effect Of Seedmentioning
confidence: 94%
“…Chemical scorodite syntheses are generally conducted at pH 1.0 or lower [2,6,8,9,25]. Fujita et al (2009) chemically synthesized stable scorodite particles at the pH range of 0.3-1.0, but higher pH levels (pH > 1.2) negatively affected scorodite stability [17].…”
Section: Effect Of Initial Phmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be done for example at elevated temperatures, near the boiling point of water (80-95 °C) and under controlled supersaturated conditions. (Singhania et al, 2005;Fujita et al, 2008) Crystalline Scorodite is at least 100 times less soluble than its amorphous counterpart (FeAsO4 · xH2O[am]) (Krause and Ettel, 1989;Langmuir et al, 2006;Bluteau & Demopoulos, 2007) and given its high arsenic content (in comparison to the Fe (III)-As(V) co-precipitates as mentioned above) has been advocated for the fixation of arsenic-rich wastes. (Filippou & Demopoulos 1997;Fujita et al, 2008) At even higher temperatures (>100 °C, the hydrothermal precipitation range) during autoclave hydrothermal processing of copper (Berezowsky et al, 1999) and gold (Dymov et al, 2004) sulphide feedstock's, other crystalline phases than Scorodite are reported to form some of which exhibit equal or better stability than Scorodite (Swash & Monhemius, 1994;Dutrizac & Jambor, 2007.…”
Section: Introductionmentioning
confidence: 99%